Medicinal Plants Used to Treat Evil Eye Illness in Ethiopia: A Systematic Review - Daniel Tadesse; Getinet Masresha; Moges Lemlemu (The Scientific World Journal)
Conclusion and Recommendations: This review shows that many medicinal plants are used to treat evil eye illnesses in traditional medical practices in Ethiopia. Hence, further investigation of commonly utilized plant species for the same purpose is recommended. In addition, the documentation of indigenous herbal knowledge and conservation of commonly utilized traditional medicinal plants should be strengthened.